Sintesis dengan Metode Hidrotermal dan Karakterisasi Senyawa Berstruktur Aurivillius Bi4Ti3O12 [Synthesis of Aurivillius Bi4Ti3012 using Hydrothermal Method and Structured Compound Characterization] - Muhammad Rizal; Ismunandar Ismunandar (Jurnal Matematika & Sains, 2007)
The Bi4Ti3O12 powder was synthesized using hydrothermal method from Bi2O3/TiO2 and Bi(OH)3/TiO2 as starting materials and NaOH as mineralizer. Characterization of the obtained powder was carried out using X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR). High purity of Bi4Ti3O12 powder was obtained from reaction at 240 Â°C, 72 hours and NaOH of 3 M for both starting materials. The obtained diffraction patterns were similar with the standard pattern (PDF, no. 35-0795). The FTIR spectrum revealed two absorption peaks at 587 and 827 cm-1, which are characterictic absorbtion of octahedral TiO6 in Bi4Ti3O12 structure.